2006
DOI: 10.1111/j.1440-1827.2006.01983.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of wild‐type estrogen receptor β protein in human breast cancer: Specific correlation with HER2/neu overexpression

Abstract: Expression of estrogen receptor beta (ERbeta) protein in human breast cancer and correlation with clinicopathological factors have been reported by many investigators, but many of them used ERbeta antibodies that react with both wild-type ERbeta (ERbetawt) and splicing variant isoform. Therefore, the frequency and correlation with clinicopathological factors of ERbetawt expression remain to be established. In the present study a monoclonal antibody EMR02, specific for ERbetawt, was used in formalin-fixed paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 18 publications
3
37
0
2
Order By: Relevance
“…In contrast, there is a positive association between ERβ and HER2 expression in high-grade ERα-breast cancer [98]. In invasive ductal carcinoma, HER2 overexpression correlates inversely with ERα levels, but positively with ERβ [90]. Thus, ERα−/ERβ+ tumors tend to express HER2 but not PR, whereas ERα+/ERβ+, like ERα+/ERβ− tumors, tend to express PR but not HER2.…”
Section: Coexpression Of Erβ With Erα and Other Potential Markers In mentioning
confidence: 90%
See 3 more Smart Citations
“…In contrast, there is a positive association between ERβ and HER2 expression in high-grade ERα-breast cancer [98]. In invasive ductal carcinoma, HER2 overexpression correlates inversely with ERα levels, but positively with ERβ [90]. Thus, ERα−/ERβ+ tumors tend to express HER2 but not PR, whereas ERα+/ERβ+, like ERα+/ERβ− tumors, tend to express PR but not HER2.…”
Section: Coexpression Of Erβ With Erα and Other Potential Markers In mentioning
confidence: 90%
“…Studies examining correlations between ERβ and PR have reported either no correlation [88,89], a weak positive correlation [81,90], or an inverse correlation [91]. One confounding variable for interpreting these studies is that there are two populations of tumors -one containing ERβ only, and another expressing both ERα and ERβ, which may have different phenotypes.…”
Section: Coexpression Of Erβ With Erα and Other Potential Markers In mentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 Some studies demonstrated that HER2/neu breast cancers have elevated IL-8 expression and showed a correlation between HER2 and ERβ expression. 26,27 Based on these findings, the authors proposed the existence of a possible HER2/ERβ/IL-8 expression axis. To test this hypothesis, the authors first performed immunohistochemical staining on breast cancer clinical samples and found a positive association between IL-8 and ERβ.…”
mentioning
confidence: 99%